SPOUSAL RELATIONS IN ISLAM: RIGHTS, DUTIES, AND CODE OF CONDUCT (International journal of artificial intelligence, 2025)
This article explores the relationship between husband and wife in terms of rights, duties, and ethics based on Islamic sources. Drawing upon verses from the Holy Qur’an and authentic hadiths, it analyzes the responsibilities of the husband, the rights of the wife, and the sexual, spiritual, financial, and social obligations within marriage. Inspired by the sayings of the Prophet Muhammad (peace be upon him), the article highlights key Islamic values such as patience, compassion, honesty, obedience, and kind treatment. It also addresses threats to family stability such as divorce, jealousy, harshness, and impatience. This scholarly work offers an Islamic perspective on resolving contemporary family issues.